(untitled) (Ameghiniana, 2013)
This note describes a new species of crocodile, Notosuchus lepidus, from the Argentine Mesozoic, the old red sandstone of Neuquen. The species is distinguished from the other described forms by the skull very compressed, with the bones little sculptured and the synphisis very narrow.